1982
DOI: 10.1136/bmj.284.6318.782
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim resistance in hospitals.

Abstract: RAUNO MANTYJARVI, MD, professor of clinical microbiology in Finland was similar to that in a London hospital just before plain trimethoprim was registered for use in Britain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…SPREAD OF RESISTANCE The use of TMP, either alone or in combination with sulfonamides, appears to be an important factor in the development and spread of TMP resistance (24,43,58,70), particularly in a hospital setting (41,43). In outpatients, however, a relationship between consumption and the development of resistance is not always evident (44).…”
Section: Attempts To Suppress Development Andmentioning
confidence: 96%
See 2 more Smart Citations
“…SPREAD OF RESISTANCE The use of TMP, either alone or in combination with sulfonamides, appears to be an important factor in the development and spread of TMP resistance (24,43,58,70), particularly in a hospital setting (41,43). In outpatients, however, a relationship between consumption and the development of resistance is not always evident (44).…”
Section: Attempts To Suppress Development Andmentioning
confidence: 96%
“…In industrialized countries, such as the United Kingdom and Finland, TMP resistance tends to be a problem in hospitals, particularly in geriatric units (4,41,43). In a hospital study in Finland, TMP resistance was found in 38% of urinary tract isolates (Pseudomonas spp.…”
Section: Spread Of Tmp Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…was logically followed with less HIV related infections (4). Less antimicrobial agents use is possibly responsible for the phenomenon of the reversibility of antimicrobial resistance also in pathogens colonizing in the respiratory tracts of children with HIV on active antiretroviral therapy.…”
Section: Methodsmentioning
confidence: 99%
“…After multipoint inoculation, plates were incubated at 35°C for 18 h (6). Resistance breakpoints used were 8 ,ug/ml for TMP and 512 ,g/ml for SMX (6). E. coli ATCC 25922 and Staphylococcus aureus ATCC 25923 were used as control strains.…”
mentioning
confidence: 99%